Pengaruh Variasi Suhu dan Kecepatan Udara Terhadap Penurunan Kadar Air Keripik Pisang - Mohammad Agus Rifa'i; Fatkhur Rohman; M. Muslimin Ilham (Prosiding Seminar Nasional Ilmu Teknik, 2026)
Drying is a critical stage in the production of banana chips because it determines the final moisture content, texture, product quality, and storage stability. Many small and medium-sized enterprises (SMEs) continue to use conventional sun drying, which depends heavily on weather conditions and often produces inconsistent drying results. This study investigated the influence of drying temperature and air velocity on the reduction of moisture content in banana chips using a batch-type dryer. Two temperature levels (60°C and 70°C) and two air velocity levels (2 m/s and 3 m/s) were applied, while observations were conducted every 30 minutes for a total drying period of 90 minutes. The experimental data were analyzed using Mixed Analysis of Variance (Mixed ANOVA). Statistical analysis revealed that drying time had a significant effect on moisture reduction, whereas variations in drying temperature and air velocity did not significantly influence the moisture content at the 95% confidence level. Although not statistically significant, the treatment combination of 70°C and 2 m/s tended to produce the lowest final moisture content. These findings indicate that drying duration plays a more dominant role than the tested operating conditions in reducing the moisture content of banana chips.